If someone could point out where I've gone wrong, I would appreciate it.
9x^2 - 18x + 3 = 0
x^2 - 2x + 1/3 = 0
x^2 - 2x = -1/3
x^2 - 2x + 1 = 1 - 1/3
(x-1)^2 = 2/3
x - 1 = square root 2/3
x = 1 plus/minus square root 2/3
The answer should be 1 plus/minus the square root 6 over 3.
Where did I go wrong? Thanks.
9x^2 - 18x + 3 = 0
x^2 - 2x + 1/3 = 0
x^2 - 2x = -1/3
x^2 - 2x + 1 = 1 - 1/3
(x-1)^2 = 2/3
x - 1 = square root 2/3
x = 1 plus/minus square root 2/3
The answer should be 1 plus/minus the square root 6 over 3.
Where did I go wrong? Thanks.